The Chemical and Physical Properties of Poly(ε-caprolactone) Scaffolds Functionalised with Poly(vinyl phosphonic acid-co-acrylic acid). (22nd September 2011) - Bassi, A. K.; Gough, J. E.; Zakikhani, M.; Downes, S.
Abstract : There is a clinical need for a synthetic alternative to bone graft substitute (BGS) derived from demineralised bone matrix. We report the electrospinning of Poly( ε -caprolactone) (PCL) to form a 3-dimensional scaffold for use as a synthetic BGS. Additionally, we have used Poly(vinyl phosphonic acid-co-acrylic acid) (PVPA) to improve bone formation. Fibres were formed using a 10% w/v PCL/acetone solution. Infrared spectroscopy confirmed that the electrospinning process had no effect on the functional groups present in the resulting structure. The electrospun scaffolds were coated with PVPA (PCL/PVPA), and characterised. The stability of the PVPA coating after immersion in culture medium was assessed over 21 days. There was rapid release of the coating until day 2, after which the coating became stable. The wettability of the PCL scaffolds improved significantly, from 123.3 ± 10.8° to 43.3 ± 1.2° after functionalisation with PVPA. The compressive strength of the PCL/PVPA scaffolds (72 MPa) was significantly higher to that of the PCL scaffold (14 MPa), and an intermediate between trabecular and cortical bone (7 MPa and 170 MPa, resp.). The study has demonstrated that the PCL/PVPA scaffold has the desired chemical and biomechanical characteristics required for a material designed to be used as a BGS.